Instalasi Pengolah Air Bersih untuk Mendukung Kualitas Kesehatan Masyarakat Desa Dayah Leubu Kecamatan Ulim Pidie Jaya Pasca Bencana Siklon Senyar 2025 - Zahrul Fuadi; Nasaruddin Nasaruddin; Muhammad Syukri; Sofia Sofia; Mujiburrahmad Mujiburrahmad; Aulia Rahman; Syarawi Muhammad; Arya Rudi Nasution; Misbahussudur Misbahussudur; Aura Dwi Kesha (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This community service activity aims to improve access to safe and sustainable clean water in Dayah Leubue Village, Ulim District, Pidie Jaya Regency, following the flood disaster caused by Cyclone Senyar in 2025. Specific targets include the availability of a functioning clean water treatment plant, improved water quality that meets health standards, enhanced community knowledge and skills in system operation and maintenance, and the establishment of a village-level clean water management institution. The implementation method uses a community development approach based on appropriate technology and cross-disciplinary collaboration. The resulting outputs include one clean water treatment plant producing water of proven potable quality and one solar power plant for emergency lighting. This activity also strengthened community health capacity through clean water and sanitation awareness training. Overall, this activity has provided clean water access to the community of Dayah Leubue Village, Ulim District, Pidie Jaya, and is expected to improve their quality of life by reducing the risk of health problems caused by water and sanitation issues.